Massonia saniensis (Asparagaceae, Scilloideae), a new species from Lesotho, southern Africa - Wetschnig, Wolfgang; Martínez-Azorín, Mario; Pinter, Michael; Brudermann, Andreas; Deutsch, Gerfried; Crespo, Manuel B.; Dold, Anthony P.; Pfosser, Martin (Phytotaxa, 2014)
As part of a taxonomic revision of the genus Massonia, a new species, M. saniensis is here described from Lesotho (southern Africa). This species is at first sight similar to both M. wittebergensis and M. jasminiflora, but it differs in vegetative, floral, and molecular characters as well as by its distribution. A complete morphological description of the new species and data on biology, habitat, and distribution are presented.